The Role of Fatty Acid Oxidation in the Metabolic Reprograming of Activated T-Cells - Byersdorfer, Craig Alan (Frontiers in Immunology, 2014)
Activation represents a significant bioenergetic challenge for T cells, which must undergo metabolic reprogramming to keep pace with increased energetic demands. This review focuses on the role of fatty acid metabolism, both in vitro and in vivo, following T cell activation. Based upon previous studies in the literature, as well as accumulating evidence in allogeneic cells, I propose a multi-step model of in vivo metabolic reprogramming. In this model, a primary determinant of metabolic phenotype is the ubiquity and duration of antigen exposure. The implications of this model, as well as the future challenges and opportunities in studying T cell metabolism, will be discussed.